Carbon fixation from mineral carbonates - Brandon S. Guida (Nature Portfolio, 2017)
Evidence showing that carbonates can directly supply CO2 for autotrophy is lacking. Here, using stable isotope analyses and NanoSIMS imaging, the authors show that a model euendolith, Mastigocoleus testarum strain BC008, derives the majority of its biomass carbon from the mineral carbonates it excavates.